2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037205
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation, electrode choice and challenges in human skin memristor measurement

Abstract: Recording of the passive electrical properties of human skin is a well-established method in clinical applications and research. By applying a small constant voltage or current to the skin, its conductance can be determined without changing it. If a strong electrical signal is applied, the conductance can change. In fact, such nonlinear effects in skin can be observed and it has been shown that the skin acts like a memristor. These nonlinear properties of human skin are not studied systematically yet and hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Changes in skin properties due to electrodes (i.e., occlusion, electrolyte effects or skin irritation) or instrumentation [polarization of skin or electro-osmosis when using DC measurement (Pabst et al, 2017a,b)].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in skin properties due to electrodes (i.e., occlusion, electrolyte effects or skin irritation) or instrumentation [polarization of skin or electro-osmosis when using DC measurement (Pabst et al, 2017a,b)].…”
Section: Discussionmentioning
confidence: 99%
“…It was tried to reset the different initial conditions and to ensure galvanic contact through the sweat ducts by adding the one minute of workout at the stationary bike before the experiment started. It was shown that the non-linear electrical properties of human skin can change significantly before and after workout (see [ 24 ]). However, one minute on the stationary bike was very likely too short to cause any thermal sweating.…”
Section: Discussionmentioning
confidence: 99%
“…A tub filled with saline solution (0.9% NaCl, electrical contact was realized by 6 Ag/AgCl electrodes that were placed at the well of the tub) in which the foot was placed was used as a large M-electrode to minimize the contribution of the corresponding skin memristor to the measurement (see [ 24 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Beyond SCR, other measures also allow inference on SNA and, thus, on the same psychological variables. It remains to be determined whether measures such as skin potential and skin susceptance (Tronstad et al, ) or the memristor properties of the skin (Pabst, Tronstad, & Martinsen, ) yield additional information or can help reduce noise in the inverse inference.…”
Section: Psychophysiological Models For Different Measurementsmentioning
confidence: 99%